IAPP toxicity activates HIF1α/PFKFB3 signaling delaying β-cell loss at the expense of β-cell function - Chiara Montemurro (Nature Portfolio, 2019)
Type 2 diabetes is associated with islet amyloid deposits derived from islet amyloid polypeptide (IAPP) expressed by β-cells. Here the authors show that IAPP misfolded protein stress induces the hypoxia inducible factor 1 alpha injury repair pathway and activates survival metabolic changes mediated by PFKFB3.